2018
DOI: 10.1080/23279095.2018.1429441
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment of adults with ADHD: A Delphi consensus study

Abstract: Within the clinical evaluation of adults with attention deficit hyperactivity disorder (ADHD), cognitive functions are often assessed to characterize individual cognitive problems and guide treatment planning. However, the composition of an adequate neuropsychological assessment battery remains difficult given the large number of cognitive functions that can be distinguished, the variety of available tools to assess these functions, as well as the cognitive heterogeneity that has been observed between individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 80 publications
2
58
3
1
Order By: Relevance
“…50 Nonetheless, EF tests could still be useful to characterize the cognitive profile of specific individuals. 51 Despite the fact that children with RD displayed a more prominent profile of executive deficits in the present study, we also found a shared inhibitory control deficit between RD and ADHD children on one of the tasks, even after controlling for age and nonverbal reasoning. Inhibitory control deficits are described as an important endophenotype for the study of ADHD.…”
Section: Discussioncontrasting
confidence: 84%
“…50 Nonetheless, EF tests could still be useful to characterize the cognitive profile of specific individuals. 51 Despite the fact that children with RD displayed a more prominent profile of executive deficits in the present study, we also found a shared inhibitory control deficit between RD and ADHD children on one of the tasks, even after controlling for age and nonverbal reasoning. Inhibitory control deficits are described as an important endophenotype for the study of ADHD.…”
Section: Discussioncontrasting
confidence: 84%
“…Continuous performance tests are considered a key component of any ADHD assessment because they assess attention, vigilance, processing speed, impulsivity, and response inhibition (Advokat, Martino, Hill, & Gouvier, 2007;Fuermaier, Fricke, de Vries, Tucha, & Tucha, 2019). Furthermore, greater variability in response time on CPTs is clearly related to attention lapses and distractibility (Adams, Roberts, Milich, & Fillmore, 2011).…”
Section: Recommendationsmentioning
confidence: 99%
“…Continuous performance tests (CPTs) are considered a key component of any ADHD assessment and are currently the most popular objective laboratory-based measures to support a clinical diagnosis of ADHD [32-34]. The majority of CPT tasks measure selective attention, sustained attention, and impulsivity [35-37] and can be used alongside clinical evaluation to inform the diagnostic process of ADHD [38, 39].…”
Section: Introductionmentioning
confidence: 99%